2000
DOI: 10.1128/aem.66.4.1764-1766.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Motile Aeromonas Strains with the MicroScan WalkAway System in Conjunction with the Combo Negative Type 1S Panels

Abstract: This study was performed to compare the MicroScan WalkAway automated identification system in conjunction with the new MicroScan Combo Negative type 1S panels with conventional biochemical methods for identifying 85 environmental, clinical, and reference strains of eight Aeromonas species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
3
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
2
3
1
Order By: Relevance
“…The poor accuracy of MicroScan in identifying Aeromonas isolates to the species level in our study contrasted with the results of Vivas et al (21). We tested isolates of all of the Aeromonas species, and only 19.3% of such isolates were correctly identified, while Vivas et al (21) tested isolates of eight species and correctly identified 78.8% of them.…”
contrasting
confidence: 93%
See 3 more Smart Citations
“…The poor accuracy of MicroScan in identifying Aeromonas isolates to the species level in our study contrasted with the results of Vivas et al (21). We tested isolates of all of the Aeromonas species, and only 19.3% of such isolates were correctly identified, while Vivas et al (21) tested isolates of eight species and correctly identified 78.8% of them.…”
contrasting
confidence: 93%
“…If these results were correct, this would agree with those of Vivas et al (21), who stated that this is the most common clinical species. However, by using the 16S rDNA RFLP method, we found that A. hydrophila only represented 8.1% of the 490 clinical isolates tested (unpublished data).…”
supporting
confidence: 89%
See 2 more Smart Citations
“…vaccine for homologous and heterologous virulent strains in rainbow trout [32,33]. The aroA mutant shows typical A. hydrophila reactions using the MicroScan WalkAway automatic identification system after 48 h of incubation in Combo panels [34], and the interruption of the aroA gene in the mutant strain was confirmed by PCR assays according to Casco´n Soriano et al [35]. Stock cultures of the strain were maintained at ÿ80 (C with 30% glycerol, and were routinely grown in tryptic soy agar (TSA, Cultimed) at 22 (C.…”
Section: Aeromonas Hydrophila Aroa Strain and Culture Mediamentioning
confidence: 99%